Analisis Tingkat Penerapan Good Agricultural Practices (GAP) Terhadap Usaha Tani Sawi Di Kecamatan Delta Pawan - Akbar, Wahris Tursadi; Maswadi, Maswadi; Kurniati, Dewi Kurniati (Universitas Galuh, 2025)
Good Agricultural Practice, or GAP for short, is a set of guidelines for good and correct mustard plant cultivation that emphasizes safety, health, and community welfare while aiming for high productivity, high-quality products, maximum profit, and environmental friendliness. In this instance, the author wishes to investigate